Strengthening the Competitive Advantages of the Batik Creative Industry During Pandemic - Hiras Pasaribu; Karyono Karyono; H. KRT. Nur Suhascaryo; Alp. Yuwidiantoro (International Journal of Entrepreneurship and Sustainability Studies, 2021)
The obstacle for the creative batik industry during the Covid-19 pandemic is that it is not easy to reach the market. Because before the pandemic, the agents, buyers, and consumers could come to the place where the product was made. To get out of these difficulties, business actors must adapt to innovate, including by using business digitization technology, so that market coverage will be wider and building innovations so that product quality can compete. In order for SMEs to quickly adapt during the COVID-19 pandemic, they must join forces to form a community portal that drives the batik industry. This study aims to determine the effect of corporate governance, product innovation, digitalization-based information technology, and the effectiveness of management control on the competitive advantage of SMEs in the creative industry of batik craftsmen in districts and cities in Yogyakarta. The research method used is a survey method to 55 managers of 127 Creative Industry SMEs batik craftsmen in all districts and city of Yogyakarta. Primary data collection using a questionnaire with the Likert Scale. In accordance with the consideration of data values and hypotheses, this study uses an appropriate statistical analysis, namely the Partial Least Square (PLS) method. The results show that corporate governance has no significant effect on the competitive advantage of SMEs, while product innovation, utilization of information technology based on business digitization, and the effectiveness of management controls have a positive effect on competitive advantage.